Ethnobotanical survey of useful bromeliads (Bromeliaceae) in the Juchipila Valley, Zacatecas, México - López-García, Raúl; Muro-Pérez, Gisela; López-Santiago, Marco Andrés; Sánchez-Salas, Jaime (Ecosistemas y Recursos Agropecuarios, 2023)
The Bromeliaceae family in Mexico is composed of 422 species, of which 18 are found in Zacatecas. The objective was to describe the current uses of bromeliads in the Juchipila Valley and contribute to the knowledge of the state flora. Botanical specimens were collected in tianguis, religious festivities, orchards and natural vegetation. Forty-one informants were interviewed in three municipalities. Identification was carried out with dichotomous keys and comparison with herbarium specimens. Five species belonging to 2 genera were recorded, including the first record of the genus Bromelia L. for Zacatecas. Tillandsia usneoides standing out as the species with the highest economic value. The bromeliads in the Juchipila Valley are used mainly for ornamental purposes. Studies are suggested to estimate the effects of harvesting and document management practices on wild populations. The record of a new genus confirms the importance of continuing with ethnobotanical explorations in the southern region of Zacatecas.
Keywords: tianguis, interviews, new record, ornamental, Tillandsia usneoides; Seleccionado:tianguis, interviews, new record, ornamental, Tillandsia usneoides